Deep Turbulence as a Novel Main Driver for Multi-Specific Toxic Algal Blooms: The Case of an Anoxic and Heavy Metal-Polluted Submarine Canyon That Harbors Toxic Dinoflagellate Resting Cysts - Rodríguez-Villegas, Camilo; Pérez-Santos, Iván; Díaz, Patricio A.; Baldrich, Ángela M.; Lee, Matthew R.; Saldías, Gonzalo S.; Mancilla-Gutiérrez, Guido; Urrutia, Cynthia; Navarro, Claudio R.; Varela, Daniel A.; Ross, Lauren; Figueroa, Rosa I. (Microorganisms (Basel), 2024)
Over the recent decades, an apparent worldwide rise in Harmful Algae Blooms (HABs) has been observed due to the growing exploitation of the coastal environment, the exponential growth of monitoring programs, and growing global maritime transport. HAB species like Alexandrium catenella—responsible for paralytic shellfish poisoning (PSP)—Protoceratium reticulatum, and Lingulaulax polyedra (yessotoxin producers) are a major public concern due to their negative socioeconomic impacts. The significant northward geographical expansion of A. catenella into more oceanic-influenced waters from the fjords where it is usually observed needs to be studied. Currently, their northern boundary reaches the 36°S in the Biobio region where sparse vegetative cells were recently observed in the water column. Here, we describe the environment of the Biobio submarine canyon using sediment and water column variables and propose how toxic resting cyst abundance and excystment are coupled with deep-water turbulence (10−7 Watt/kg) and intense diapycnal eddy diffusivity (10−4 m2 s−1) processes, which could trigger a mono or multi-specific harmful event. The presence of resting cysts may not constitute an imminent risk, with these resting cysts being subject to resuspension processes, but may represent a potent indicator of the adaptation of HAB species to new environments like the anoxic Biobio canyon.